IDENTIFICATION OF VESICULAR ARBUSCULAR MYCORRHIZA (VAM) FROM SOIL AND ITS POTENCY IN REDUCING DISEASE DEVELOPMENT (Phytophthora sp.) ON 5 CITRUS ROOTSTOCK - Dwiastuti, Mutia Erti; Widyaningsih, Sri; Wicaksono, Rudi Cahyo; Agustina, Dina; Triasih, Unun (El-Hayah : Jurnal Biologi, 2019)
Phytophthora spp. is one of the fungal pathogens that kills plants on several kinds of the citrus rootstock. In other countries, it is reported that disease pathogens were reduced in roots containing Vesicular Arbuscular Mycorrhiza (VAM interaction). However, in Indonesia, there is less information about the effect of VAM on the roots of citrus plants against root disease caused by Phytophthora sp. This study aimed to identify VAM in citrus roots and study the potential of VAM in controlling root rot of Phytophthora sp. on five types of the citrus rootstock. The research was carried out at the Phytopathology Laboratory, Indonesian Citrus, and Subtropical Fruits Research Institute (ICSFRI). Phytophthora spp. and VAM samples originated from several citrus centers endemic to Phytophthora were collected. VAM was isolated from the rhizosphere area of citrus plants, while Phytophthora sp. was isolated from infected plant roots. The fungus isolates were isolated, purified, then identified through references. The test of the potential of VAM in increasing resistance of root diseases caused by Phytophthora sp. was performed at the screen house in ICSFRI. The results of the study showed that VAM was identified in 39 gardens in 6 districts from samples collected in 49 yards in 10 regions of citrus centers. The dominant VAM genus is Glomus sp. with the highest density of spores was originated from Ponorogo area. The results of the identification of Phytophthora morphologically showed a diversity of Phytophthora, namely P. parasitica, P. palmivora, and P. citrophthora. The test of the potential of VAM in increasing plant resistance to Phytophthora results showed that Kanci, JC, RL, and Volkameriana varieties inoculated with Phytophthora sp. and Glomus sp. have higher plant height than healthy plants.